The metabolic chronic disease prevention program in Saint Kitts and Nevis: a dietary recall study - Yang, Jin-Han; Matthew-Duncan, Latoya; Laws, Hazel; Isles, Sheneil; Shu, Yi-Fang; Lee, Yi; Lin, Lu-Xiang; Kang, Shu-Yong; Hsu, Hsueh-Wen; Hwu, Chii-Min; Chen, Hsiang-Chi; Su, Guan-Yu (Frontiers in Nutrition, 2025)
BackgroundThe Federation of Saint Christopher and Nevis faces a growing prevalence of non-communicable diseases (NCDs) due to dietary transitions, sedentary lifestyles, and unhealthy behaviors. This study aims to assess food and nutrient intake, nutrient deficiencies, and health behaviors among residents of the country.MethodsThe study was conducted from February to March 2023. Individuals who lived in Saint Kitts and Nevis for at least 6 months, aged more than 18 years were randomly selected from 14 administrative parishes based on the population ratio. A 24-h dietary recall method was used to collect food and nutrient intake data. Demographic, physical activity, food intake frequency and other health behaviors were also collected. Descriptive statistical analysis was conducted on the baseline characteristics and nutritional intake, and logistic regression was used to assess the effects of demographic characteristics on unhealthy behaviors. Statistical analysis was performed using SPSS.ResultsA total of 212 individuals (156 from Saint Kitts and 56 from Nevis) underwent the survey. The median BMI was 28.0, with 52.8% reporting no physical activity in the past week. The median caloric intake was 1737.8 kcal/day, with males consuming more than females. The proportional of total daily caloric intake was 46.3, 16.9 and 34.3% for carbohydrate, protein, and lipid, respectively. Other nutrients intake data revealed suboptimal calcium and vitamin A consumption, with 565.7 mg/day for calcium and 223.2 μg/day for vitamin A. The median sodium intake was 2914.9 mg, while potassium intake was 2044.3 mg. A sodium-to-potassium ratio was 1.43, which was above the WHO’s recommended value.ConclusionIn the study, we found the population of Saint Kitts and Nevis exhibits nutritional imbalance and low physical activities. These findings highlight the need for interventions to improve nutrition and promote healthy behaviors to deal with the rising burden of NCDs in the region.